2012
DOI: 10.4172/2168-9881.1000110
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction of Cadmium from Contaminated Soil Assisted By Microbial Biopolymers

Abstract: Heavy metal contaminated soils remain as a challenging and essential task for environmental engineering. Phytoremediation (plant-based remediation) is effective for the mitigation of large area surface soil contamination, but needs long time and the efficiency is not high. Chemical agents could increase heavy metal bioavailability in soil and bring greater accumulation in plants, but also pose risks to soil, plant growth and ground water environment. In this study, microbial biopolymers, mainly composed of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Most of the studied EPS are negatively charged, due to the dominance of carboxyl and hydroxyl functional groups, in different proportions depending on EPS composition ( Ding et al, 2018 ). The main factors influencing metal biosorption by EPS are related to the binding sites or their chemical nature, such as pH, metal content, ionic strength, surface properties, as well as EPS molecular weight and degree of branching ( Guibaud et al, 2003 ; Fukushi, 2012 ). For instance, it was demonstrated that the structural conformation of xanthan affects Cu–xanthan bond strength.…”
Section: Ecological Functionsmentioning
confidence: 99%
“…Most of the studied EPS are negatively charged, due to the dominance of carboxyl and hydroxyl functional groups, in different proportions depending on EPS composition ( Ding et al, 2018 ). The main factors influencing metal biosorption by EPS are related to the binding sites or their chemical nature, such as pH, metal content, ionic strength, surface properties, as well as EPS molecular weight and degree of branching ( Guibaud et al, 2003 ; Fukushi, 2012 ). For instance, it was demonstrated that the structural conformation of xanthan affects Cu–xanthan bond strength.…”
Section: Ecological Functionsmentioning
confidence: 99%
“…Similarly, Abd El-Ghany and Attia [ 85 ] reported a decrease in Cl − ion in faba beans inoculated with an EPS-producing Azotobacter chroococcum strain in combination with melatonin. However, most of the studied bacterial EPS are negatively charged, due to the dominance of carboxyl and hydroxyl functional groups [ 87 , 88 , 89 , 90 , 91 ], indicating that the decrease in chloride anion concentration in PGPR-inoculated plants might not be related to the adsorption capacity of Cl − by EPS.…”
Section: Salinitymentioning
confidence: 99%
“…The role of bacterial EPS in heavy metal bioremediation has been extensively studied [ 89 ]. Moreover, PGPR are used to accelerate heavy metal phytoremediation [ 151 ].…”
Section: Heavy Metalmentioning
confidence: 99%